Observations From NOAA's Newest Solar Proton Sensor - B. T. Kress; J. V. Rodriguez; A. Boudouridis; T. G. Onsager; B. K. Dichter; G. E. Galica; S. Tsui (Space Weather)
Abstract Space weather instrumentation on board the National Oceanic and Atmospheric Administration's (NOAA's) newest Geostationary Operational Environmental Satellite (GOES)‐R series includes the Solar and Galactic Proton Sensor (SGPS), which has been collecting data since January 8, 2017. SGPS supports real‐time alerts of solar energetic particle events at the NOAA Space Weather Prediction Center (SWPC) and provides data to the space science community, advancing basic space science research and understanding of space weather effects on satellite systems. The first GOES‐R series spacecraft, GOES‐16, was launched on November 19, 2016. A series of solar particle events in September 2017 enabled cross‐calibration of GOES‐16 SGPS with the Energetic Particle Sensors on GOES‐13 and ‐15. This paper is intended as a resource for SGPS data users, including comparisons with legacy GOES energetic particle measurements, corrections applied to SGPS Level‐2 data, important caveats, background level fluxes, and measurements of trapped magnetospheric protons.